Risk and self‐managing chronic joint pain: looking beyond individual lifestyles and behaviour. Issue 6 (14th July 2015) - Morden, Andrew; Jinks, Clare; Ong, Bie Nio
Abstract Self‐managing chronic musculoskeletal pain is predominantly framed within a discourse of modifying behaviour, or lifestyle risk factors such as diet, weight loss and exercise by policymakers, researcher and clinicians. Little research has been conducted which explores how 'risk' is understood or encountered by those with joint pain and how it may relate to self‐management. Drawing from serial interviews and a diary study with 22 participants, the findings demonstrate that people with chronic pain engage in a process of assessing and adapting to hazardous or pain conferring situations in relation to daily activities. 'Risks' are embedded within a dialectic between corporeal experience and the design features of everyday social environments. Self‐management, in this context, is not necessarily solely related to following clinical advice, rather it includes dealing with 'risks' of pain, hazards relating to bodily limitations and the environment, and ensuring the ability to continue with valued activities. Findings contribute to sociological understandings of self‐management and risk while demonstrating the limits of viewing self‐management as an individualised endeavour of changing behaviour.